Framework to build component based e-Manufacturing / Goh Ki Wei - Goh , Ki Wei (2004)
This documentation report is a fully description about our project. The project title is to build a technique and framework to develop a component-based e-Manufacturing system. This project is undertaken by a group of four members. The framework consists of four modules, which are Sales module, Material Requirements Planning (MRP) module, Production module, and Material Management module. Fulfilling minimum business requirements for a manufacturer is the ultimate goal of this project. The essence of the framework 1s able to support reusable approach. Furthermore, framework is extensible or easy to evolve as the business requirement is changing. We have conducted survey and research upon the cutting edges technologies, which could be leveraged and will be adopted in the development of the project. We have come across the literature review and study about the current available technology for operating system, database management system, data access paradigms, system architecture, system development tool, and programming language. The software development life cycle of this project is actually following a particular development methodology. incremental and iterative development approach will be ideal to develop the component-based framework. This methodology comprises of a sequence of steps along the software development phases, including preliminary investigation, system analysis, system design, implementation, system integration, and system testing. Meanwhile, Unified Modelling Language (UML) is being used to modelling and visualise the physical and conceptual of the software development process phases.